ANALISIS PENGARUH PERSEPSI DUKUNGAN KELUARGA, DUKUNGAN TEMPAT KERJA DAN KEBIJAKAN KESEIMBANGAN KEHIDUPAN-KERJA TERHADAP KINERJA KARYAWAN DENGAN KESEIMBANGAN KEHIDUPANKERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Tenaga Kesehatan Perempuan di Kecamatan Banyumanik) - Desy Mustikaningrum; Mirwan Surya Perdhana (Faculty of Economics and Business Diponegoro University, 2022)
The aim of this study was to analyze the effect of Perceived Family Support, Workplace Support, and Work-Life Balance Policies on Employee Performance through Work-life Balance as Mediator. This study was conducted on female health workers who remained working during the pandemic of Covid-19. This study used primary data sources distributed through the research questionnaires. This Study used purposive sampling that distributed to female health workers in Banyumanik district. This study used Partial Least Square using the SmartPLS 3.3.9 to determine the path coefficient, and the direct or indirect effect of exogenous variables on endogenous variables. The results of statistical test analysis using alpha = 0.05. Meanwhile, the results of this study showed that Perceived Family Support and Workplace Support has a positive and significant effect on work-life balance, as well as work-life balance has a positive and significant effect on employee performance. Whereas, Work-Life Balance Policies has no significant effect on Work-Life Balance